Comment on: "Reactive wetting of solders on Cu and Cu6Sn5/Cu3Sn/Cu substrates using wetting balance". (1st April 2021) - Dušek, Karel
Abstract: In this contribution, as comments to the paper in Scripta Materialia, Volume 55, Issue 9, Pages 823-826, November 2006, will be shown that the residual force marked as Fd is not correctly described. This residual force is recorded during wetting force measurement by wetting balance method, and it was wrongly used as a part of withdrawal force F wd . The correct relation between residual force Fd and withdrawal force Fwd will be explained more deeply in this comment. Graphical abstract: Image, graphical abstract